Depression, Language, and Affect: An Examination of the Influence of Baseline Depression and Affect Induction on Language. (June 2016) - Bernard, Jared D.; Baddeley, Jenna L.; Rodriguez, Benjamin F.; Burke, Philip A.
Literature suggests that depression influences how individuals communicate. However, no studies examine the impact of affective state on language. The current study examined the influence of depression and affective state on linguistic style. Findings suggest that depression and temporary negative moods both affect pronoun use, but depression influences use of first-person pronouns, whereas negative affect influences use of third-person pronouns.